Microsurgical seminal reconstruction; our experiences in a single institute - Hibi, Hatsuki; Sugie, Miho; Ohori, Tadashi; Sonohara, Megumi; Fukunaga, Noritaka; Asada, Yoshimasa (Nagoya journal of medical science, 2020)
We assessed the contribution of microsurgical seminal reconstruction to achieving natural conception in conjunction with advanced assisted reproductive technologies. Ninety obstructive azoospermic subjects who underwent microsurgical seminal reconstruction were evaluated. Vasovasostomy (VV) was undertaken in 45 subjects whereas vasoepididymostomy (VE) in 45, respectively. VV was performed by employing a two microlayer anastomotic technique, whilst VE was undertaken using double needle longitudinal vaspepididymostomy (LIVE). Patency was achieved in 41 VV (91.1%), and 25 VE (55.6%) cases. In cases where patency was achieved, pregnancy and healthy delivery were recorded following natural intercourse in 7/41 (17.0%) VV, and in 7/25 (28.0%) VE cases. Where patency was not achieved, the use of cryopreserved sperm for intracytoplasmic sperm injection (ICSI), resulted in a healthy delivery in 4/4 (100%) VV and 14/21 (66.6%) in VE subjects. Although natural pregnancy was achieved only in a limited number of subjects treated (14/90; 15.6%), sperm harvested during surgery and cryopreserved for future ICSI use proved valuable, doubling the overall delivery rate (32/90; 36.6%). Surgical intervention is considered to be a useful technique in order to allow the possibility of a natural conception and by harvesting sperm at the same time contributes to the cost-effectiveness.